Culture and Sexuality: Cognitive–Emotional Determinants of Sexual Dissatisfaction Among Iranian and New Zealand Women. Issue 5 (10th April 2018) - Abdolmanafi, Atefe; Nobre, Pedro; Winter, Sam; Tilley, P.J. Matt; Jahromi, Reza Ghorban
Abstract: Background: Several studies have demonstrated that culture plays a fundamental role in individuals' beliefs, attitudes, and values toward sexuality, and influences their ability to enjoy sex. It follows that culture may influence sexual satisfaction or dissatisfaction. Aim: To examine and compare cognitive–emotional variables related to women's sexual dissatisfaction in Iran and New Zealand. Methods: In total, 196 Iranian women and 207 New Zealand women participated in the study, answering questionnaires evaluating dysfunctional sexual beliefs, automatic thoughts, emotional and sexual response during sexual activity, as well as sexual satisfaction. Outcomes: Sexual beliefs were measured by the Sexual Dysfunctional Beliefs Questionnaire, thoughts and emotional responses were measured by the Sexual Modes Questionnaire, and sexual satisfaction was measured by the Sexual Satisfaction Index. Results: Findings indicated that in both Iranian and New Zealand women, failure and disengagement thoughts, lack of erotic thoughts, and emotions of fear during sexual activity were significant predictors of sexual dissatisfaction. Besides these common predictors, results also indicated that sexual conservatism and women's sexual passivity beliefs, sexual abuse thoughts, and fear during sexual activity were significant predictors of sexual dissatisfaction in Iranian women. Beliefs of sexual desire and pleasure as a sin; age-related beliefs; and emotions such as sadness, disillusion, and hurt were significant predictors of sexual dissatisfaction in New Zealand women. Clinical Translation: The present findings could facilitate a better understanding of cultural differences in the roles played by dysfunctional sexual beliefs, negative automatic thoughts, and negative emotions during sexual activity, and the value of these beliefs, thoughts, and emotions in predicting sexual dissatisfaction. Conclusions: The strength of this study is in providing an examination of the role of culturally bound beliefs in predicting sexual dissatisfaction in women from different cultural backgrounds. Limitations include the lack of evaluation of psychological and interpersonal variables that may impact on women's sexual dissatisfaction. These findings suggest that there may be a role of culture in shaping beliefs, attitudes, and values toward sexuality; and provide evidence for the effect of cognitive–emotional variables in predicting women's sexual dissatisfaction.